Beyond Inclusion: Mobilising Queer Pedagogy to Reframe Inclusive Practice Within Youth, Community and Educational Space - Hannah Poklad (Youth)
Beyond Inclusion aims to explore and revise embedded societal norms which are reproduced throughout practice. In this paper, Queer will be utilised not only to disrupt, but to divest from the cis-normative and hetero-normative standards which are often cemented by the fields within which we work. Informed by collected narratives, ethnohistory and theoretical developments in pedagogy, Beyond Inclusion will explore the multifaceted and multidisciplinary application of Queer pedagogy in order to celebrate Queer, and use Queer to celebrate all which deviates from normalcy. With the intention of empowering youth, community and educational pedagogues to feel confident in Queering their pedagogy, this paper aims to agitate systems of oppression by unusualising the usual, and usualising the unusual, by illuminating what is considered to be normal and why, and how normalcy impacts those who reside on the outskirts of hegemonic culture. Readers will be invited to mobilise Queer, in order to re-examine, reimagine and reconstruct new and Queered ways of upholding anti-oppressive practice. This research will present pragmatic actions which have been informed by questionnaires and interviews with Queer participants, and aim to improve lived experiences for young Queer people and Othered communities. This body of work emphasises negotiated practice, in that the reader will not be provided with definitive solutions, but instead be autonomised in deducing and producing their own knowledge and actions from the information presented.